Comprehensive Molecular Characterization of Escherichia coli Isolates from Urine Samples of Hospitalized Patients in Rio de Janeiro, Brazil - Campos, Ana Carolina C.; Andrade, Nathália L.; Ferdous, Mithila; Chlebowicz, Monika A.; Santos, Carla C.; Correal, Julio C. D.; Lo Ten Foe, Jerome R.; Rosa, Ana Cláudia P.; Damasco, Paulo V.; Friedrich, Alex W.; Rossen, John W. A. (Frontiers in Microbiology, 2018)
Urinary tract infections (UTIs) are often caused by Escherichia coli. Their increasing resistance to broad-spectrum antibiotics challenges the treatment of UTIs. Whereas E. coli ST131 is often multidrug resistant (MDR), ST69 remains susceptible to antibiotics such as cephalosporins. Both STs are commonly linked to community and nosocomial infections. E. coli phylogenetic groups B2 and D are associated with virulence and resistance profiles making them more pathogenic. Little is known about the population structure of E. coli isolates obtained from urine samples of hospitalized patients in Brazil. Therefore, we characterized E. coli isolated from urine samples of patients hospitalized at the university and three private hospitals in Rio de Janeiro, using whole genome sequencing. A high prevalence of E. coli ST131 and ST69 was found, but other lineages, namely ST73, ST648, ST405 and ST10 were also detected. Interestingly, isolates could be divided into two groups based on their antibiotic susceptibility. Isolates belonging to ST131, ST648 and ST405 showed a high resistance rate to all antibiotic classes tested, whereas isolates belonging to ST10, ST73, ST69 were in general susceptible to the antibiotics tested. Additionally, most ST69 isolates, normally resistant to aminoglycosides, were susceptible to this antibiotic in our population. The majority of ST131 isolates were ESBL-producing and belonged to serotype O25:H4 and the H30-R subclone. Previous studies showed that this subclone is often associated with more complicated UTIs, most likely due to their high resistance rate to different antibiotic classes. Sequenced isolates could be classified into five phylogenetic groups of which B2, D and F showed higher resistance rates than groups A and B1. No significant difference for the predicted virulence genes scores was found for isolates belonging to ST131, ST648, ST405 and ST69. In contrast, the phylogenetic groups B2, D and F showed a higher predictive virulence score compared to phylogenetic groups A and B1. In conclusion, despite the diversity of E. coli isolates causing UTIs, clonal groups O25:H4-B2-ST131 H30-R, O1:H6-B2-ST648 and O102:H6-D-ST405 were the most prevalent. The emergence of highly virulent and MDR E. coli in Brazil is of high concern and requires more attention from the health authorities.